The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0192623310386499
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative and Nonproliferative Lesions of the Rat and Mouse Hepatobiliary System

Abstract: The INHAND Project (International Harmonization of Nomenclature and Diagnostic Criteria for Lesions in Rats and Mice) is a joint initiative of the Societies of Toxicologic Pathology from Europe (ESTP), Great Britain (BSTP), Japan (JSTP) and North America (STP) to develop an internationally-accepted nomenclature for proliferative and non-proliferative lesions in laboratory animals. The purpose of this publication is to provide a standardized nomenclature and differential diagnosis for classifying microscopic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
433
4
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 505 publications
(481 citation statements)
references
References 222 publications
21
433
4
4
Order By: Relevance
“…These lipid-like vacuoles are in contrast to glycogen-like vacuoles where there is irregular lacy intracytoplasmic clearing and no nuclear displacement. Phospholipidosis in rodent livers can be induced by a number of cationic amphiphilic drugs, and affected hepatocytes have variably sized clear cytoplasmic vacuoles that cannot be unequivocally distinguished from lipid based on morphology alone (38,39). Although we did not see elevated liver triglyceride levels in these animals, it is possible that this may have appeared with a longer duration of treatment.…”
Section: Table 2 Summary Of Tissue Retinoid Levels From Experimentscontrasting
confidence: 59%
See 1 more Smart Citation
“…These lipid-like vacuoles are in contrast to glycogen-like vacuoles where there is irregular lacy intracytoplasmic clearing and no nuclear displacement. Phospholipidosis in rodent livers can be induced by a number of cationic amphiphilic drugs, and affected hepatocytes have variably sized clear cytoplasmic vacuoles that cannot be unequivocally distinguished from lipid based on morphology alone (38,39). Although we did not see elevated liver triglyceride levels in these animals, it is possible that this may have appeared with a longer duration of treatment.…”
Section: Table 2 Summary Of Tissue Retinoid Levels From Experimentscontrasting
confidence: 59%
“…One concern about such an approach to the treatment of obesity, however, may be our observation of microvesicular lipidosis in some of the liver specimens in WIN 18,446-treated animals. Vacuolation of hepatocytes may be due to lipids, phospholipidosis, and glycogen accumulation, all of which are removed from the tissues during routine processing and embedding, leaving vacuoles behind (38). On H&E-stained sections, medium to large, clear, round cytoplasmic vacuoles that occasionally displaced the nucleus within centrilobular to midzonal hepatocytes were noted.…”
Section: Table 2 Summary Of Tissue Retinoid Levels From Experimentsmentioning
confidence: 99%
“…These pathologies can be in association with inflammation processes in other organs and while the cells of the hepatic parenchyma have the flexibility to adapt to changing physiological demands, with reversible functional and morphological alterations, sufficient stress or noxious stimuli may lead to inability to maintain homeostasis and adverse cellular adaptations. The morphological response to injurious stimuli depends on the nature of the injury and its severity and duration (Thoolen et al 2010). Helal et al (2011) detected that noise exposure showed some vacuolated hepatocytes with enlarged nuclei of the endothelial lining compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth in Mdr2 KO livers is multinodular, and HCC tends to develop within an adenoma (as a focus of tumor progression). The histological composition of grossly detectable hepatic nodules was semiquantitatively determined based on reported classification criteria (Thoolen et al 2010). In order to analyze sample sets based on histological content, we classified samples as "adenoma" when scoring a variable content in adenomatous tissue without any detectable presence of carcinoma, "lowgrade HCC" with a histologic content of carcinoma ≤ 50%, and "high-grade HCC" when the carcinoma content was higher than 50%.…”
Section: Identification Of Differentially Expressed Peaksmentioning
confidence: 99%